John Damascus’s Church-Singing Brotherhood in Nizhny Novgorod at Beginning of 20th Century - N. E. Arkhipova (Научный диалог)
The organization, composition, financial condition and activities of the John Damascus’s singing brotherhood are considered. The relevance of the study is associated with the need to revive spiritual and moral values in modern Russian society. The novelty of the esearch lies in the fact that for the first time, according to the chronicle of the church press, the functioning of the brotherhood was reconstructed, the choir of which consisted of representatives of the city clergy, and the conductors were professional musicians. The author notes that, despite the increase in the number of performers in peacetime, the unstable composition of the choir did not allow them to achieve high performing skills. It is shown that the brotherhood performed organizational, missionary, spiritual, educational, charitable  functions. It is proved that the work of the brotherhood contributed to the activation of concert and choral activities in the city, helped to preserve the ancient singing tradition, on the one hand, and introduced the audience to modern sacred music on the other hand. It is emphasized that in the conditions of the expansion of secularization at the beginning of the 20th century, charitable spiritual concerts  organized  by the brotherhood helped to maintain, strengthen and develop religious and moral feelings, thoughts, moods in listeners. It is concluded that the deteriorating living conditions during the war years, and then revolutionary events stopped the functioning of the organization.